Tinjauan Literatur Sistematis: Loker Pintar - Alfian Rizqi, Irfan (Jetri : Jurnal Ilmiah Teknik Elektro, 2024)
Security systems are essential to prevent theft or other criminal acts in order to prevent the increase in theft crime rates from year to year. To overcome these challenges, this research designs a system that is integrated with a website, aiming to monitor the availability of lockers, perform the booking process, and open and lock lockers using Near Field Communication (NFC) cards. The purpose of this research is to review and analyze the application of NFC in locker design. The research conducted a literature evaluation that included 19 studies from scientific journals. The findings suggest that there are many research trends, methods, and architectures used in predictive analytics with IoT in the context of locker usage. Keywords: Security, Smart Locker, NFC, Internet of Things